2020
DOI: 10.3390/su12030893
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships between Stationary Occupancy and Building Energy Loads in US Educational Buildings–Case Study

Abstract: Building energy systems are designed to handle both permanent and temporary occupants. Permanent occupants are considered the base energy load while temporary occupants are considered a temporary or additional load. Temporary occupancy is potentially the most difficult to design as the number of temporary occupants varies more significantly than permanent occupants. This case study was designed to investigate the effect of occupancy on energy loads, i.e. the relationship between occupancy and building energy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, Chen, Jiang, and Xie (2018) reported that BLE and Wi-Fi detection systems have limitations as the users may turn off Wi-Fi or Bluetooth on their devices and may have multiple devices. Lee, Chong, and Chou (2020) monitored stationary (such as faculty members and graduate students) and non-stationary occupants (such as students) in the Arizona State University building using Ethernet traffic flow and Wi-Fi connections, respectively. The authors noted the limitations of assuming occupant types solely based on whether they connect their devices to Wi-Fi or Ethernet.…”
Section: A Comparison Of Occupancy Detection and Monitoring Systemsmentioning
confidence: 99%
“…However, Chen, Jiang, and Xie (2018) reported that BLE and Wi-Fi detection systems have limitations as the users may turn off Wi-Fi or Bluetooth on their devices and may have multiple devices. Lee, Chong, and Chou (2020) monitored stationary (such as faculty members and graduate students) and non-stationary occupants (such as students) in the Arizona State University building using Ethernet traffic flow and Wi-Fi connections, respectively. The authors noted the limitations of assuming occupant types solely based on whether they connect their devices to Wi-Fi or Ethernet.…”
Section: A Comparison Of Occupancy Detection and Monitoring Systemsmentioning
confidence: 99%
“…This means that building energy and services systems (such as HVAC, lighting, plug-loads etc.) in residential buildings have to remain operating in order to provide energy, thermal comfort and ventilation even during weekends [14] . Conversely, offices and schools will have less internal heat gains and less operation time due to less occupants and by scaling back their activities, which will result in a drop of the energy demand especially during the weekdays.…”
Section: Introductionmentioning
confidence: 99%